1987
DOI: 10.1073/pnas.84.14.5004
|View full text |Cite
|
Sign up to set email alerts
|

High activity of N-alpha-benzyloxycarbonyl-L-lysine thiobenzyl ester serine esterase and cytolytic perforin in cloned cell lines is not demonstrable in in-vivo-induced cytotoxic effector cells.

Abstract: Recent observations have suggested striking similarities between complement-mediated and cell-mediated lysis. Both pathways share the terminal insertion of channels into target membranes, and unique esterases have been postulated to participate in the activation of cytolytic effector molecules. Since killer-specific esterases and channel-forming proteins can be demonstrated in in vitro cell lines, it is important to ascertain that the described esterase and channelforming proteins are also present in killer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Natural killer cells and cytotoxic T lymphocytes are known to contain perforin in their cytoplasmic granules in vitro.69 However, until recently, there has been no evidence showing the role of perforin in cell-mediated cytotoxicity primed in vivo. [22][23][24] et a125 demonstrated the expression of perforin mainly in CD8 positive cytotoxic T lymphocytes and in a small population of natural killer-like cells during lymphocytic choriomeningitis virus infection. Later, this was confirmed at the transcriptional level by in situ hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…Natural killer cells and cytotoxic T lymphocytes are known to contain perforin in their cytoplasmic granules in vitro.69 However, until recently, there has been no evidence showing the role of perforin in cell-mediated cytotoxicity primed in vivo. [22][23][24] et a125 demonstrated the expression of perforin mainly in CD8 positive cytotoxic T lymphocytes and in a small population of natural killer-like cells during lymphocytic choriomeningitis virus infection. Later, this was confirmed at the transcriptional level by in situ hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, evidence of adaptive immune response was found among those genes significantly overexpressed within C2 cancers, including markers of T-cell activation (CD8A, Granzyme B; ref. 29…”
Section: Resultsmentioning
confidence: 99%
“…Initial studies had reported few, if any, cytolytic granules in mouse primary peritoneal exudate lymphocytes, suggesting that these cells use a different lytic mechanism. [9][10][11][12] Podack and coworkers, however, had demonstrated perforin mRNA in mouse primary peritoneal exudate T-lymphocytes, supporting the evidence that all cytolytic T-cells tested expressed perforin. 13 A strong correlation exists between cytolytic potential and perforin mRNA expression in human large granular lymphocytes, NK cells, gamma/delta T-cells and CD8-positive Tcells.…”
Section: Objective: Perforin Is a Specific Marker Of Functionally Actmentioning
confidence: 81%